On abundance, phenology and natural history of Geophilomorpha from a mixedwater inundation forest in Central Amazonia (Chilopoda) - Wellington de Morais, José (1997)
Five terricolous species of Geophilomorpha were collected in a mixcdwater inundation forest near Manaus/AM, Brazil: Rihautia (Schizoribautia) di!ficilis Pereira et al., 1995, Rihautia (S.) centralis (Silvestri, 1907) (Gcophilidae), Schendvlurus continuus Pereira et al., 1995, S.janauarius Pereira ct al., 1995 and Pectiniunguis ascendens Pereira et al., 1994 (Schendylidae). Reproduction occurred in the soil. R. (S.) difficilis andP. ascend ens inhabit the first 7.0 em, whereas R. (S.) centralis, S. continuus and Sjanauarius live to a soil depth of I 0.5 em. P. ascendens and S.janauarius were most abundant, representing 39. 1 %and 28.3% of all catches, respectively (n= 22.1 ±21. 7 ind./m2/month on average). A survival strategy observed as a reaction to the flood period was that all these terricolous species pass the aquatic phase of several months' duration on trees by means of vertical migrations. Our data reconfirm that the mixedwater inundation forest represents an ecotone: S. continuus is also found in non-flooded primary upland forests near Manaus, whereas P. ascendens and R. (S.) centralis occur in a blackwater inundation forest in the lower basin of the Negro River as well.